Intrapartum antibiotic exposure and infectious diseases in childhood – a population-based cohort studyResearch in context - Mikael Hakkola; Sofia Ainonen; Eveliina Ronkainen; Minna Honkila; Marika Paalanne; Tytti Pokka; Eero Kajantie; Niko Paalanne; Terhi Ruuska-Loewald (EBioMedicine)
Summary: Background: Intrapartum antibiotics are used to prevent group B streptococcus disease in newborn infants. We hypothesised that intrapartum antibiotic exposure is associated with the occurrence of childhood infectious diseases because it influences the development of the gut microbiome. Methods: The cohort for this population-based study comprised vaginally delivered children born in Northern Finland in 2007–2018. We used structured electronic medical records linked to comprehensive national registers. Primary outcome was the number of infectious disease episodes leading to an emergency room visit, outpatient hospital visit, or hospitalisation from birth until five years of age. Findings: Analyses were performed on 9733 children (48.8% girls) exposed to intrapartum antibiotics and on 35,842 unexposed children (49.9% girls). Exposure to intrapartum antibiotics was associated with increased risk of any infectious disease episode at the ages 7−28 days (adjusted incidence rate ratio [aIRR] 1.30, 95% CI 1.10−1.54) and 1−2 years (aIRR 1.10, 95% CI 1.02–1.18). The occurrence of urinary tract infections was associated with the exposure to intrapartum antibiotics whereas the occurrence of severe infections caused by pathogens susceptible to penicillin was reversely associated with the exposure to intrapartum antibiotics. Interpretation: Maternal intrapartum antibiotics were associated with the occurrence of infectious diseases in the offspring. The observed associations appeared to depend on bacterial pathogens and their antimicrobial susceptibility to penicillin. Funding: Pediatric Research Foundation, Alma och K.A. Snellman Foundation, Orion Research Foundation, Päivikki and Sakari Sohlberg Foundation, Finnish Medical Foundation, Academy of Finland, Finland.